Differential Effects of Antiepileptic Drugs on Neonatal Outcomes - Pennell, P.B. (2012)
Offspring of women with epilepsy (WWE) on AEDs are at increased risks for major congenital malformations and reduced cognition. They may be at risk for other adverse neonatal outcomes. WWE on carbamazepine (CBZ), lamotrigine (LTG), phenytoin (PHT), or valproate (VPA) monotherapy were enrolled in a prospective, observational, multicenter study of the neurodevelopmental effects of AEDs. The odds ratio for small for gestational age (SGA) was higher for VPA vs. PHT, VPA vs. LTG, and CBZ vs. PHT. Microcephaly rates were elevated to 12% for all newborns and 12-months-old, but normalized by age 24-months. Reduced Apgar scores occurred more frequently in the VPA and PHT groups at 1 minute, but scores were near normal in all groups at 5 minutes. This study demonstrates increased risks for being born SGA in the VPA and CBZ groups, and transiently reduced Apgar scores in the VPA and PHT groups. Differential risks amongst the AEDs can help inform decisions about AED selection for women during childbearing years.